1975
DOI: 10.1021/ja00857a035
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic ligand ring size effects on complex stabilities and kinetics. Copper(II) complexes of cyclic polythiaethers

Abstract: 34% yield. An increase in the diene concentration resulted in a decrease in the yield of the silacyclopentene, and none of this product was obtained when the hexamethylsilirane-2,3-dimethyl-l,3-butadiene reaction was carried out (1 5 hr at 70°) in the absence of a diluent, although the tetramethylethylene yield was 40%. With some other dienes (e.g., trans,trans-2,4-hexadiene) no dimethylsilylene adducts were obtained under the conditions found to be successful with 2,3-dimethyl-1,3-butadiene. One may speculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 1 publication
2
9
0
Order By: Relevance
“…36 Without being able to quantify it exactly, the association constant for the [Cu(II)-TTCD] complex is estimated as being very low in view of the forward wave position situated at the extreme right of the cyclic voltammogram (Figure 5). This result is consistent with literature data, 17,37 where values of log K 1 o ) 2.5 (in a methanol/water (4:1) mixture at 25 °C) are reported. Nevertheless, numerous authors showed that cyclic thioether ligands complex Cu + ions very strongly.…”
Section: Resultssupporting
confidence: 94%
“…36 Without being able to quantify it exactly, the association constant for the [Cu(II)-TTCD] complex is estimated as being very low in view of the forward wave position situated at the extreme right of the cyclic voltammogram (Figure 5). This result is consistent with literature data, 17,37 where values of log K 1 o ) 2.5 (in a methanol/water (4:1) mixture at 25 °C) are reported. Nevertheless, numerous authors showed that cyclic thioether ligands complex Cu + ions very strongly.…”
Section: Resultssupporting
confidence: 94%
“…Recently, however, we have shown that the cyclic tetrathia ethers2•' represent an excellent series of ligands for the systematic investigation of the dependence of kinetic parameters on ligand ring size, presumably reflecting the influence of ligand structure upon bond formation and rupture processes. 4 Of even greater interest is the very recent discovery that the copper(II) thia ether complexes exhibit unusual spectral and redox properties similar to those found in the blue copper proteins.5™7 Since the blue copper protein phenomena have frequently been ascribed to the presence of tetrahedral or five-coordinate copper(II),8™10 a rigorous determination of the structural features inherent in the copper(II) thia ether complexes was deemed a matter of the utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…The copper(II) complexes formed with both [18]aneS 4 N 2 and [18]aneS 4 O 2 exhibit a strong S-to-Cu charge-transfer band around 390 nm and a somewhat weaker band around 580 nm, consistent with the absorption bands found previously for similar copperpolythioether complexes. [33][34][35] The molar absorptivity values for all complexes were determined using solutions of known concentration as shown in Table 1.…”
Section: Uv/vis Characterization Of Copper(ii)-ligand Complexesmentioning
confidence: 99%